The capital market and economic cycles: an empirical approach to the austrian theory - da Silva Oliveira, Glaucio Israel; Pires de Sousa, Paulo Roberto; S. Moreira, Tito Belchior; dos Santos, Luciano Balbino (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
This article aims to ascertain the impact that cyclical and monetary macroeconomic variables have on the capital market, as well as, in addition to this, to verify if this repercussion effect empirically confirms some of the postulates of the Austrian theory of business cycles (ABCT), such as the significance of currency in business cycles and its relative impact on production stages. Using data from the year 2009 to 2019, the research was divided into two analyses, the first consisting of econometric tools (through the robust least squares method) and the second based on statistical tools. The results show that the monetary repercussion has a lot of potential to generate cycles in the stock markets, in addition, they reveal that the stages furthest from final consumers are the ones that most suffer impacts from a possible monetary policy.